Tradisi Politik Melayu: Analisis Pengangkatan dan Pergantian Kekuasaan di Kesultanan Palembang Darussalam: Malay Political Tradition: The Appointment and Succession Analysis of The Sultanate of Palembang Darussalam - Mohammad Syawaludin; Muhammad Sirajudin Fikri; Yulion Zalpa (Society, 2019)
This study aims to determine and explore how Islam and Malay as an intertwined entity influence the formation of political institutions in the Sultanate of Palembang, especially influencing the appointment and succession of the Sultan. This study is the result of qualitative research based on a literature review using interpretive analysis techniques. In the practice of Islam in Indonesia, cultural values ??of non-Islamic religions are maintained and practiced by Islamic entities such as practices in the replacement of the King and Sultan. A theoretical approach to society by looking at the evolution of kings approached to explain the history of state administration and the transition of power, combined with Elite; Political Culture, and Cultural Politics. The results of this study found that the system of appointment and change of power in the Sultanate of Palembang, namely the existence of its characteristics associated with a blend of Malay and Javanese culture. Differences in political culture greatly influence the process of succession that occurs. Malay culture which emphasizes more on its economy in the maritime field and Arabic symbols will be different from Javanese culture which is more agrarian and syncretic.